A User-Centric Perspective of 6G Networks: A Survey - Stamatia F. Drampalou; Dimitris Uzunidis; Anastasios Vetsos; Nikolaos I. Miridakis; Panagiotis Karkazis (IEEE Access)
6G currently stands at the forefront of wireless communications research, offering numerous enhancements over previous generations. New key performance indicators (KPIs) have been defined, including microsecond-level latency and increased data transmission capacity. These advancements are expected to catalyze the development of immersive applications such as the metaverse, digital twins, and Industry 6.0 technologies. To achieve these KPIs, emerging technologies like edge computing, THz communications, and cell-free systems must be leveraged. Artificial Intelligence (AI) and Machine Learning (ML) are anticipated to play a crucial role in optimizing 6G networks while enhanced security and privacy, both in infrastructure and user communications, are also key considerations. Current research suggests a shift towards a more user-centric network architecture, tailored to individual user requirements, in contrast to the service-oriented approach of 5G. This survey article aims to shed light on this user-centric concept by comprehensively reviewing the various aspects of 6G network architecture from a user-centric perspective.